Hubungan Hipertensi Dengan Mikroalbumin Urin Pada Usia Diatas 40 Tahun - Cristianto Sagala, Rudy; Lim, Hadyanto; Singh, Surjit (Jurnal Kedokteran Methodist, 2024)
Background : Hypertension is the risk factor for cardiovascular disease and it is related with endothelial dysfunction. The disease is marked by microalbuminuria. Microalbuminuria is related with the damage of endothelial glomerulus and predictor of chronic renal failure. Microalbuminuria increases albuminuria. This will manifest as endothelial damage of the glomerulus. This study is to assess the relation between hypertension and microalbuminuria in people over 40 years of age Methods : in 13 subjects of essential hypertension in Medan, basic data down and their blood pressure and microalbumin checked in Clinical Laboratory of Prodia on Jl. S. Parman No. 17/223 G Medan. This research use cross section study. Shapiro-Wilk test conducted to find out normal distribution data and Pearson correlation test conducted to find out the relation between the variables. The significant score is P<0.05. Results : 6 subjects in this research were in category of A2 (moderate): 3-30 mg/mmol creatinine.7 subject in this study were in category A3(Severe): >30 mg/mmol creatinine. There was correlation (r = 0.898, p = 0.000) between systolic hypertension and microalbuminuria and the correlation between diastolic and microalbuminuria was (r = 0.574, p = 0.040). Conclusion: Hypertension is related with the increase of microalbuminuria for both systolic hypertension and diastolic Hypertension.